Comparative Performance of Some Insecticides and Botanicals against Chilli Fruit Borer (Helicoverpa armigera) - Akter, M. M. Rahman*, S.M.M. Rahman; A. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> : The study was carried out in the experimental field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from February to June 2007 to determine the comparative efficacy of some chemical insecticides and botanicals against chilli fruit borer. The experiment comprised with twelve treatments and among them first six (T1-T6) were the application of insecticide and others (T7-T11) were botanicals. Treatments were T1: Sumicidin @ 6.0 ml/2 litre of water at 7 days interval; T2: Malathion @ 6.0 ml/2 litre of water at 7 days interval; T3: Ripcord @ 3.0 ml/2 litre of water at 7 days interval; T4: Marshal @ 6.0 ml/2 litre of water at 7 days interval; T5: Diazinon @ 6.0 ml/2 litre of water at 7 days interval; T6: Suntaf @ 2.5 ml/2 litre of water at 7 days interval; T7: Allamanda leaf extract @ 0.5 kg/2 litre of water at 7 days interval; T8: Neem leaf extract @ 0.5 kg/2 litre of water at 7 days interval; T9: Garlic clove extract @ 0.5 kg/2 litre of water at 7 days interval; T10: Ginger rhizome extract @ 0.5 kg/2 litre of water at 7 days interval; T11: Onion bulb extract @ 0.5 kg/2 litre of water at 7 days interval; T12: Untreated control. In total cropping season the lowest percentage of fruit infestation by number (5.72%) was recorded from the treatment T4 which was statistically similar (6.22%) with the treatment T8 and the highest (24.90%) was recorded from untreated control treatment which was closely followed (17.39%) by the treatment T5 and T11 (16.48%) and T10 (15.37%) respectively. Fruit infestation reduction over control by number estimated as the highest value (77.03%) was recorded from the treatment T4, while the lowest (30.16%) was recorded from T5 treatment. Fruit infestation reduction over control by weight was estimated and the highest value was (63.35%), recorded from the treatment T4, while the lowest (22.84%) reduction of fruit infestation over control was from the treatment T5. Highest weight of fruit yield (30.60 t/ha) was recorded from the treatment T4 and the lowest yield (24.48 t/ha) of fruit was recorded from untreated control treatment. Among different treatments as whole botanicals (T7-T11) were more effective than those of the chemicals insecticides (T1-T6).